Patient preferences for Remote cochlear implant management: A discrete choice experiment - Catherine Sucher; Richard Norman; Emma Chaffey; Rebecca Bennett; Melanie Ferguson (PLoS ONE, 2025)
Background The opportunity to assess cochlear implant outcomes remotely provides the potential to streamline delivery of care for cochlear implant users. However, the conditions required for its implementation into clinic systems must be fully understood to ensure success and sustainability. The objectives of this study were to (i) use a discrete choice experiment quantify the preferences of cochlear implant users when considering use of Cochlear Remote CheckTM, a remote assessment service, and (ii) explore the perceptions, insights and attitudes of CI users that may influence utilisation of a remote service. Design A discrete choice experiment was administrated to Australian adult cochlear implant users via an online survey. Participants chose between pairs of hypothetical clinical service options for three different clinical scenarios (acute care, troubleshooting and long-term review). Participants answered a series of questions focusing on how and when remote services should be discussed and offered within their hearing journey. Results A total of 124 adult cochlear implant users completed the survey. Conditional logit analysis revealed the strongest participant preference was clinician continuity for assessment review, followed by low service costs. They preferred to receive assessment results within one week of completion, but not by videoconference/call in the acute care scenario. Only 12% of participants preferred in-clinic visits for all scenarios. Notably, 100% of participants felt that cochlear implant users should be made aware of remote service opportunities available to them. Conclusion Study participants placed high importance on clinician continuity, but preferences for timing and delivery of results were less pronounced. This information can help to inform customisation of remote services by individual clinics. Costs and payment infrastructure for providing remote care require careful consideration. Whilst there is an appetite for use of Remote CheckTM alongside clinic visits, it is not suitable for, nor preferred by, all cochlear implant users.